2022
DOI: 10.3847/1538-4357/ac7460
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Viscous Dissipation on Collisional Growth and Fragmentation of Dust Aggregates

Abstract: Understanding the collisional behavior of dust aggregates consisting of submicron-sized grains is essential to unveiling how planetesimals formed in protoplanetary disks. It is known that the collisional behavior of individual dust particles strongly depends on the strength of viscous dissipation force; however, impacts of viscous dissipation on the collisional behavior of dust aggregates have not been studied in detail, especially for the cases of oblique collisions. Here we investigated the impacts of viscou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 43 publications
(68 reference statements)
6
32
0
Order By: Relevance
“…However, the contribution of the rolling displacement is negligible for ξ crit 3.2 nm. In addition, Arakawa et al (2022) confirmed that contributions of sliding and twisting displacements also play a minor role; they are one order of magnitude smaller than E break .…”
Section: Interparticle Rolling Motionmentioning
confidence: 64%
See 3 more Smart Citations
“…However, the contribution of the rolling displacement is negligible for ξ crit 3.2 nm. In addition, Arakawa et al (2022) confirmed that contributions of sliding and twisting displacements also play a minor role; they are one order of magnitude smaller than E break .…”
Section: Interparticle Rolling Motionmentioning
confidence: 64%
“…We performed three-dimensional numerical simulations of collisions between two equal-mass dust aggregates. The numerical code used in this study is identical to that developed by Arakawa et al (2022), which considered the viscous drag for normal motion and also considered friction torques for tangential motions.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Large impact parameters decrease the tendency for sticking as only parts of the colliding NPs come into close contact and experience their mutual attraction 52 , 59 . Recently, it was shown that energy dissipation in granular aggregates of water ice leads to different aggregation and fragmentation outcomes 60 . The present work indicates that phase transformation should be considered as a possible energy dissipation channel also for aggregate collisions.…”
Section: Discussionmentioning
confidence: 99%